BIOMASS ENERGY PLANTATIONS TOGETHER WITH SLUDGE AND SEWAGE UTILIZATION AS A FACTOR OF SUSTAINABLE RURAL DEYELOPMENT - MOSIEJ, Józef; KACZMARCZYK, Agnieszka; KOMOROWSKI, Hubert; WYPORSKA, Katarzyna (Economic and Environmental Studies, 2020)
EU targets on increasing the share of renewable energy in total energy generation from the present 7% to 12% in 2010 reąuires an additional annual production of 53 million tons of wood by 2010 (if the present trend is continued only 10 million additional tons will be produced annually). Europe’s common agricultural policy [CAP, 2004] is shifting towards development and diversification of economic activities, enabling multiple activities and alternative income. These two goals can be reached by biomass production on short rotation plantations (SRPs). Biomass cultivated in order to generate energy, can be used in a wide variety of biomass conversion products and processes, which fali into four major categories: combustion, gasification, hydrolysis and fermentation, which can produce electricity, heat, combined heat and power and ethanol, respectively [Ciechanowicz, 2003; Szlachta, 2005; Nowicki, 2003], The economic advantages of using SRPs for energy production are also very important eg. decreased emissions of CO2 into the atmosphere [Karaczun and Kassenberg, 2001].